2011
DOI: 10.4269/ajtmh.2011.10-0393
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Surveillance of Leptospira in Domestic and Peri-Domestic Animals in Mahalla City, Gharbeya Governorate, Egypt

Abstract: Abstract. A survey of 179 animals (black rats, dogs, sheep, buffaloes, cattle, donkeys, weasels, and cats) for Leptospira infection was conducted in Mahalla City (Lower Egypt). Blood, urine, and kidney were collected and tested by culture, microscopic agglutination test (MAT), and/or polymerase chain reaction (PCR). Among rats, 26% were positive by PCR, including 7% that were also positive by culture for L. interrogans serovars Grippotyphosa, Pyrogenes, and Icterohaemorrhagiae. L. borpetersenii serovar Polonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 23 publications
5
41
2
1
Order By: Relevance
“…Regarding rats, a recent study (3) found that the detection rate of Leptospira antibodies was lower (23%) compared with an earlier study from Egypt (55.4%) (4) and many other reports from different parts of the world (17) (18) (19) . However, the same study (3) reported that dogs had never been evaluated as carriers of Leptospira in Egypt, and the observed seroprevalence in that study was 12%, which was similar to the seroprevalence reported in Italy (20) and Thailand (21) but much lower than that reported in Germany (22) , Mexico (23) and the USA (24) .…”
Section: Table 3 -Results Of Serotyping Of the Isolates Recovered Fromentioning
confidence: 72%
See 3 more Smart Citations
“…Regarding rats, a recent study (3) found that the detection rate of Leptospira antibodies was lower (23%) compared with an earlier study from Egypt (55.4%) (4) and many other reports from different parts of the world (17) (18) (19) . However, the same study (3) reported that dogs had never been evaluated as carriers of Leptospira in Egypt, and the observed seroprevalence in that study was 12%, which was similar to the seroprevalence reported in Italy (20) and Thailand (21) but much lower than that reported in Germany (22) , Mexico (23) and the USA (24) .…”
Section: Table 3 -Results Of Serotyping Of the Isolates Recovered Fromentioning
confidence: 72%
“…In Egypt, recent surveillance of AFI (acute febrile illness) patients revealed that among the areas tested, Mahalla city showed a higher frequency of leptospirosis compared with other regions of the country (7) (15) . Therefore, approximately four years later, another study was published providing data on the distribution of leptospirosis in animals in Mahalla (3) . Prior to this study, the most recent animal surveys in Egypt were conducted in Cairo over 20 years ago (4) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of leptospirosis in rodents, as determined by the level of antibodies raised in response to different serovars, ranges from 3.33% to 30.2% in different countries (AGUDELO-FLÓREZ et al, 2009;FELT et al, 2011;GAROUSSI et al, 2006;HALLIDAY et al, 2013;LILENBAUM, 2013;MGODE et al, 2014;MOHAMED et al, 2010;SPOHR, 2009;WANG;HE, 2013). In Brazil, leptospirosis positivity rates of 9.3% and 17% were detected in Paraná (PR) (SPOHR, 2009) and Rio de Janeiro (MARTINS; LILENBAUM, 2013), respectively.…”
Section: Introductionmentioning
confidence: 99%